Anastrozole monotherapy further improves near-adult height after the initial combined treatment with leuprorelin and anastrozole in early-maturing girls with compromised growth prediction: results from the second phase of the GAIL study - Papadimitriou, Dimitrios T.; Dermitzaki, Eleni; Christopoulos, Panagiotis; Livadas, Sarantis; Grivea, Ioanna N.; Mastorakos, George (Frontiers in Endocrinology, 2024)
Background The first phase of the GAIL study (“Girls treated with an Aromatase Inhibitor and Leuprorelin,” ISRCTN11469487) has shown that the combination of anastrozole and leuprorelin for 24 months is safe and effective in improving the predicted adult height (PAH) in girls with early puberty and compromised growth prediction by +1.21 standard deviation score (SDS; +7.51 cm) compared to inhibition of puberty alone, +0.31 SDS (+1.92 cm). Objectives and hypotheses In the second phase of the GAIL study, we assessed the adult height (AH)/near-adult height (NAH) at the end of the first phase and, in addition, the efficacy of anastrozole monotherapy thereafter in further improving NAH. Methods We measured the AH (age 16.5 years)/NAH [bone age (BA), 15 years] of the 40 girls included, divided into two matched groups: group A (20 girls on anastrozole + leuprorelin) and group B (20 girls on leuprorelin alone). Group A was further randomized into two subgroups: A1 and A2. Group A1 (n = 10), after completion of the combined therapy, received anastrozole 1 mg/day as monotherapy until BA 14 years, with a 6-month follow-up. Group A2 (n = 10) and group B (n = 20), who received only the combined treatment and leuprorelin alone, respectively, were recalled for evaluation of AH/NAH. Results AH or NAH exceeded the PAH at the completion of the 2-year initial phase of the GAIL study in all groups, but the results were statistically significant only in group A1: NAH–PAH group A1, +3.85 cm (+0.62 SDS, p = 0.01); group A2, +1.6 cm (+0.26 SDS, p = 0.26); and group B, +1.7 cm (+0.3 SDS, p = 0.08). The gain in group A1 was significantly greater than that in group A2 (p = 0.04) and in group B (p = 0.03). Anastrozole was determined to be safe even as monotherapy in Group A1. Conclusions In early-maturing girls with compromised growth potential, the combined treatment with leuprorelin and anastrozole for 2 years or until the age of 11 years resulted in a total gain in height of +9.7 cm when continuing anastrozole monotherapy until the attainment of NAH, as opposed to +7.4 cm if they do not continue with the anastrozole monotherapy and +3.6 cm when treated with leuprorelin alone. Thus, the combined intervention ends at the shortest distance from the target height if continued with anastrozole monotherapy until BA 14 years.